Middle school matters : the 10 key skills kids need to thrive in middle school and beyond--and how parents can help - Fagell, Phyllis L. (Lifelong, 2019)
"Middle school is its own important, distinct territory, and yet it's either written off as an uncomfortable rite of passage or lumped in with other developmental phases. Based on her many years working in schools, professional counselor Phyllis Fagell sees these years instead as a critical stage that parents can't afford to ignore (and though "middle school" includes different grades in various regions, Fagell maintains that the ages make more of a difference than the setting). Though the transition from childhood to adolescence can be tough for kids, this time of rapid physical, intellectual, moral, social, and emotional change is a unique opportunity to proactively build character and confidence. Fagell helps parents use the middle school years as a low-stakes training ground to teach kids the key skills they'll need to thrive now and in the future, including making good friend choices, negotiating conflict, regulating their own emotions, be their own advocates, and more. To answer parents' most common questions and struggles with middle school-aged children, Fagell combines her professional and personal expertise with stories and advice from prominent psychologists, doctors, parents, educators, school professionals, and middle schoolers themselves"--